Hell anxiety as non-pathological fear. Issue 9 (26th November 2018) - Cranney, Stephen; Leman, Joseph; Fergus, Thomas A.; Rowatt, Wade C.
ABSTRACT: For religious people, a concept of Hell as a place of eternal torment for the wicked is pervasive. However, very little research has explored the mental health implications of this belief. We investigate this by developing the Hell Anxiety Scale (HXS) and testing its relationship with other well-established measures of psychological functioning. Surprisingly, Hell anxiety was not related to dogmatism, religious fundamentalism, or overall religiosity, but primarily hinged on self-rated probability of going to Hell and belief in free will. HXS demonstrated very low correlation with the fear and anxiety subscales for neuroticism, suggesting that Hell anxiety may not be due to a tendency towards fear or anxiety, but is perhaps a rational response to personal theological premises. We also find that fear of Hell has strong relations with negative religious coping and death anxiety, thus establishing this measure's distinctiveness and construct validity.